Application of Design of Experiment Based Innovative Approach in Method Development and Validation of RP-HPLC for Estimation of Azilsartan in Bulk and Pharmaceutical Tablet Dosage Form - Deshmukh, Siddhata Arjun; Vanjari, Suvarna Sharad; Patil, Rajendra Bhagwan; Khandelwal, Kishanchandra Radheshyam (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: Azilsartan is an angiotensin II receptor blocker used in the treatment of hypertension. Using the DoE based approach in reversed-phase high-performance chromatography method was developed and validated as per ICH guidelines. Materials and Methods: The separation of Azilsartan using the Qualisil 5 BDS C18 column (250 x 4.6mm, particle size 5μ) in low-pressure gradient mode with photodiode array detector at 249nm. For optimization of chromatographic conditions for Azilsartan from its formulation with less number of experimental trials using Box-Behnken design. The critical quality attributes that are acetonitrile concentration in the mobile phase, pH of the aqueous phase and flow rate parameters were used to construct a mathematical model and study the effects of these independent factors on response such as retention time, tailing factor and theoretical plates. Analysis of Variance (ANOVA) confirmed that the three factors were significant its p-value found less than 0.05. Results: Optimized experimental conditions obtained by the DoE approach for proposed work consists of water and acetonitrile (75:25% v/v), pH 5.0 adjusted with orthophosphoric acid as a mobile phase at a flow rate 1ml/min with a retention time was found to be 3.516min. The developed method was validated as per ICH guidelines. An accuracy study was performed at three different levels and was found in the range of 98.94-100.46%. Conclusion: The method was found simple and rapid with good specificity and robustness.
Keywords: Azilsartan; ANOVA; Box-Behnken design; DoE approach; Robustness; Validation